Low-thermal-conductivity anti-ultraviolet fiber, preparation method and application of low-thermal-conductivity anti-ultraviolet fiber to light-shading and heat-shielding fabric
Through modified cellulose-based aerogel and polyacrylonitrile spinning technology, combined with NH2-MIL-125 (Ti) and porous zinc oxide nanosheets, low thermal conductivity and UV-resistant fibers were prepared, which solved the thermal insulation in the prior art and the problem of insufficient UV resistance, efficient insulation and flame retardant effects are achieved.
Patent Information
- Application Number
- CN202411837731.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to combine good thermal insulation and ultraviolet resistance, and the flame retardant performance is insufficient, which cannot meet the needs of efficient thermal insulation and ultraviolet protection.
The spinning preparation method is made using a modified cellulose-based aerogel as the core layer and polyacrylonitrile as the cortex. By adding NH2-MIL-125 (Ti) and acyl chloride polyethylene glycol to the cellulose-based aerogel, Combining composite nanomaterials such as porous zinc oxide nanosheets, composite fibers are formed to enhance their thermal conductivity, UV flame retardant and mechanical properties.
It achieves low thermal conductivity, good UV flame retardant effect and mechanical properties, improves the thermal insulation and UV resistance of the fiber, and improves the flame retardant performance.
Smart Images

Figure CN119308040A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical fibers, and in particular to a low-thermal-conductivity anti-ultraviolet fiber, a preparation method and application thereof to light-shielding and heat-shielding fabrics. Background Art
[0002] With the development of social economy, thermal insulation materials are becoming more and more common in production and life, and people's demand for thermal insulation materials is gradually increasing. In terms of clothing materials, thermal insulation textiles can keep the human body warm and avoid the cold, meeting people's needs for comfort and warmth. Among the many thermal insulation materials, in addition to increasing the thickness of the material for insulation, the most commonly used is to use materials with low thermal conductivity as thermal insulation materials. The lower the thermal conductivity of the material, the slower the heat transfer speed, thus achieving the purpose of efficient insulation. At the same time, in order to prevent the damage of ultraviolet rays in sunlight to the skin, the anti-ultraviolet function of clothing materials is also essential.
[0003] For example, Chinese patent application CN106637491A provides an anti-ultraviolet fiber, which includes the following components by mass: 23-31 parts of nylon, 3-12 parts of carbon fiber, 2.5-3.8 parts of polymethylsilsesquioxane microspheres, 3.6-5.3 parts of silane coupling agent, 15-25 parts of cyclodextrin, 12-18 parts of methyl cellulose, 15-22 parts of ultraviolet absorber, 12-15 parts of carbonized bacterial cellulose, and 8-15 parts of boron carbide.
[0004] For example, Chinese patent application CN114855291A provides a cellulose / SiO2 hybrid aerogel fiber and a preparation method thereof. The preparation method of the cellulose / SiO2 hybrid aerogel fiber comprises the following steps: wet spinning cellulose and water glass; the mass ratio of the cellulose to the water glass is 100:25-60; the water glass is sodium water glass and / or potassium water glass; the modulus of the water glass is 1.5-3.
[0005] However, none of the above methods can achieve both good thermal insulation and UV resistance, and the flame retardant properties of the above two fiber materials need to be improved. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a low thermal conductivity UV-resistant fiber, comprising the following steps: Step (1), using zinc nitrate and hexamethylenetetramine as raw materials to prepare porous zinc oxide nanosheets; the porous zinc oxide nanosheets are subjected to surface modification and functionalization treatment to obtain functionalized zinc oxide nanosheets; Step (2), in situ growing cobalt borate on the surface of the functionalized zinc oxide nanosheet to obtain a composite nanomaterial; mixing polyacrylonitrile, N,N-dimethylformamide and the composite nanomaterial to obtain a cortical spinning solution; Step (3), mixing modified cellulose-based aerogel powder and N,N-dimethylformamide to obtain a core layer spinning solution; spinning the skin layer spinning solution and the core layer spinning solution as raw materials to obtain polyacrylonitrile / aerogel composite fibers; modifying the polyacrylonitrile / aerogel composite fibers with diethylenetriamine to obtain aminated polyacrylonitrile / aerogel composite fibers; The method for preparing the modified cellulose-based aerogel powder comprises the following steps: Step S1, the cellulose nanofibers are pretreated and then reacted with hexamethylenediamine to obtain modified cellulose nanofibers; Step S2, treating polyethylene glycol to obtain chlorinated polyethylene glycol; Preparation of NH by hydrothermal method 2- MIL-125(Ti); modified cellulose nanofibers, NH 2- MIL-125(Ti) was used to prepare cellulose-based aerogel, and the cellulose-based aerogel was cross-linked and modified by poly(ethylene glycol) chloride to obtain modified cellulose-based aerogel powder; Step (4), 1,2-ethanedithiol, eugenol, and vinyl acetic acid react to obtain an intermediate product, and the intermediate product is used to modify the aminated polyacrylonitrile / aerogel composite fiber to obtain a low thermal conductivity UV-resistant fiber.
[0007] Preferably, in step (1), the preparation method of the functionalized zinc oxide nanosheets comprises: dispersing zinc nitrate and hexamethylenetetramine in deionized water, stirring to obtain a mixed solution, wherein the concentration of zinc ions in the mixed solution is 0.1-0.3 mol / L, and the molar ratio of zinc ions to hexamethylenetetramine is 1:1; storing the mixed solution in an oven at 85-95°C for 6 days, collecting the precipitate, washing, air-drying at room temperature, and heating to 240-260°C in an air atmosphere at a heating rate of 8-10°C / min and maintaining for 50-70 minutes to obtain porous zinc oxide nanosheets; Ethanol, deionized water, 28 wt% ammonia solution, and porous zinc oxide nanosheets are mixed, stirred at room temperature for 20-40 min, and then 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and 0.05 g / mL dopamine hydrochloride aqueous solution are added, and the reaction is continued with stirring for 22-26 h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain surface-modified porous zinc oxide nanosheets; wherein the amount ratio of ethanol, deionized water, ammonia solution, porous zinc oxide nanosheets, 2-mercapto-5-methoxyimidazo[4.5-b]pyridine, and dopamine hydrochloride aqueous solution is (32-64) g: (45-90) g: (0.4-0.8) mL: (3-8) g: (3-5) g: (15-25) mL; Mix surface-modified porous zinc oxide nanosheets, citric acid, p-toluenesulfonic acid, and N,N-dimethylformamide, heat to 120-140° C. in a nitrogen atmosphere, and stir to react for 3-5 hours. After the reaction is completed, centrifuge, wash, and dry to obtain functionalized zinc oxide nanosheets; wherein the mass ratio of the surface-modified porous zinc oxide nanosheets, citric acid, p-toluenesulfonic acid, and N,N-dimethylformamide is (4-6):(3.5-5.5):(0.09-0.12):(150-200); In the above process, zinc nitrate and hexamethylenetetramine are used as raw materials to prepare porous zinc oxide nanosheets with a pore size distribution of 1.3-25 nm by a template-free method; then, 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and dopamine are copolymerized on the surface of the porous zinc oxide nanosheets to form thiol heterocycle-doped polydopamine; further, the carboxyl groups in citric acid are combined with the phenolic hydroxyl groups of the thiol heterocycle-doped polydopamine through an esterification reaction to introduce multiple carboxyl groups on the surface-modified porous zinc oxide nanosheets.
[0008] Preferably, in step (2), the preparation method of the composite nanomaterial is as follows: adding cobalt nitrate hexahydrate to deionized water at a stirring speed of 600-700 r / min, then adding a functionalized zinc oxide nanosheet aqueous dispersion having a concentration of 3 mg / mL, continuing stirring for 20-40 min, then adding a sodium borohydride aqueous solution having a concentration of 0.5 mol / L, stirring for 30-50 min, centrifuging, collecting the precipitate, washing it, and drying it to obtain the composite nanomaterial; wherein the amount ratio of cobalt nitrate hexahydrate, deionized water, functionalized zinc oxide nanosheet aqueous dispersion, and sodium borohydride aqueous solution is (1.5-3) g:(500-800) g:(100-200) mL:(30-60) mL; In the above process, the carboxyl groups on the surface of the functionalized zinc oxide nanosheets are negatively charged and bind to the cobalt ions. The cobalt ions are anchored on the surface of the functionalized zinc oxide nanosheets through electrostatic interaction. By adding sodium borohydride, BH - It is adsorbed on the surface of cobalt ions and then reacts to generate cobalt borate nanosheets on the surface of functionalized zinc oxide nanosheets, thereby obtaining a composite nanomaterial.
[0009] Preferably, in step (2), in the skin spinning solution, the mass ratio of polyacrylonitrile, N,N-dimethylformamide and composite nanomaterial is 1:9:(0.1-0.3).
[0010] Preferably, in step (3), the concentration of the core layer spinning solution is 2-6 mg / mL; the spinning conditions are: the feed rate of the skin layer spinning solution is 12 mL / h, the feed rate of the core layer spinning solution is 2 mL / h, the spinning high-speed airflow drawing pressure is 0.2 MPa, the receiving distance is 60 cm, and the spinning time is 8 h.
[0011] Preferably, in step (3), the preparation method of the aminated polyacrylonitrile / aerogel composite fiber is as follows: immersing the polyacrylonitrile / aerogel composite fiber in a 35wt% diethylenetriamine aqueous solution with a bath ratio of 1:(25-35), heating to 100-120°C, stirring for reaction for 2-3h, filtering, washing, and drying to obtain the aminated polyacrylonitrile / aerogel composite fiber; In the above process, the nitrile group on the surface of the polyacrylonitrile / aerogel composite fiber reacts with the amino group at one end of diethylenetriamine to obtain the aminated polyacrylonitrile / aerogel composite fiber.
[0012] Furthermore, in step (3), the method for preparing the modified cellulose-based aerogel powder comprises the following steps: Step S1, taking a 1wt% cellulose nanofiber aqueous dispersion, adding sodium periodate thereto, stirring in the dark at room temperature for 45-50h, filtering, washing, and drying to obtain pretreated cellulose nanofibers; wherein the mass ratio of the cellulose nanofiber aqueous dispersion to the sodium periodate is (100-150):(1.6-2.4); Add hexamethylenediamine to a 0.5 wt% aqueous dispersion of pretreated cellulose nanofibers, stir and react at 28-32° C. for 5.5-6.5 h, filter, wash, and dry to obtain modified cellulose nanofibers; wherein the amount ratio of the aqueous dispersion of the pretreated cellulose nanofibers to hexamethylenediamine is (200-250) mL: (0.9-1.2) g; In the above process, the cellulose nanofibers are treated with sodium periodate, and part of the hydroxyl groups on the surface are converted into aldehyde groups, which react with the amino groups of hexamethylenediamine to introduce amino groups into the cellulose nanofibers, thereby obtaining modified cellulose nanofibers; Step S2, adding polyethylene glycol to dichloromethane, and then adding maleic anhydride and 4-dimethylaminopyridine, stirring and reacting at room temperature for 70-80 hours, and after the reaction is completed, precipitating the product with ether, washing, and drying to obtain dicarboxylated polyethylene glycol; wherein the mass ratio of polyethylene glycol, dichloromethane, maleic anhydride, and 4-dimethylaminopyridine is (3-6):(100-120):(4-7):(0.05-0.1); Dicarboxylated polyethylene glycol, 3-hydroxyglutaric acid, p-toluenesulfonic acid and N,N-dimethylformamide are mixed, heated to 120-130° C. in a nitrogen atmosphere, and stirred for reaction for 3-5 hours. After the reaction is completed, the solvent is removed by rotary evaporation at 80-90° C. to obtain polycarboxylated polyethylene glycol; wherein the mass ratio of dicarboxylated polyethylene glycol, 3-hydroxyglutaric acid, p-toluenesulfonic acid and N,N-dimethylformamide is (3.3-6.6):(1.5-3):(0.05-0.08):(80-100); Mix polycarboxylated polyethylene glycol, thionyl chloride and N,N-dimethylformamide, heat to 55-65° C. and maintain for 20-28 hours, and after the reaction is completed, rotary evaporate at 80-90° C. to obtain chlorinated polyethylene glycol; wherein the mass ratio of polycarboxylated polyethylene glycol, thionyl chloride and N,N-dimethylformamide is (4-6):(5-8):(100-120); In the above process, maleic anhydride is ring-opened and reacted with the hydroxyl group of polyethylene glycol to obtain dicarboxylated polyethylene glycol; dicarboxylated polyethylene glycol is combined with 3-hydroxyglutaric acid through an esterification reaction to introduce multiple carboxyl groups into polyethylene glycol to form polycarboxylated polyethylene glycol; the carboxyl groups of the polycarboxylated polyethylene glycol react with thionyl chloride to obtain polycarboxylated polyethylene glycol; Take 2-aminoterephthalic acid and dissolve it in a mixed solution of N,N-dimethylformamide and methanol, stir for 20-40 minutes, then add titanium isopropoxide, continue stirring for 20-40 minutes, heat to 100-120°C in a sealed environment for hydrothermal reaction for 70-80 hours, and naturally cool to room temperature after the reaction is completed, filter, wash, dry, and grind to obtain NH2-MIL-125 (Ti); wherein the mass ratio of 2-aminoterephthalic acid, N,N-dimethylformamide, methanol, and titanium isopropoxide is (2.8-5.6):(37.8-75.6):(8-16):(3-6); NH 2- MIL-125(Ti) was added to a suspension of modified cellulose nanofibers with a mass fraction of 1-1.5wt%, stirred for 10-15h, and freeze-dried at (-48)-(-42)℃ for 45-50h to obtain a cellulose-based aerogel, wherein NH 2- The mass ratio of MIL-125(Ti) and modified cellulose nanofibers is (0.5-0.1):1; Adding chlorinated polyethylene glycol to acetone, and then adding it to cellulose-based aerogel, cross-linking reaction at 85-95°C for 20-28h, then washing the aerogel with acetone, vacuum drying at 50-60°C, and grinding to obtain modified cellulose-based aerogel powder; wherein the mass ratio of chlorinated polyethylene glycol, acetone, and cellulose-based aerogel is (0.8-1.2):50:4; In the above process, acylated polyethylene glycol is used as a crosslinking agent, and the acyl chloride groups of acylated polyethylene glycol are crosslinked with modified cellulose nanofibers and NH 2- The amino groups in MIL-125(Ti) react to cross-link the cellulose-based aerogel.
[0013] Preferably, in step (4), the method for preparing the low thermal conductivity UV-resistant fiber is as follows: 1,2-ethanedithiol, eugenol, vinyl acetic acid and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 4-5 hours, and after the reaction is completed, rotary evaporation is performed to obtain an intermediate product; wherein the mass ratio of 1,2-ethanedithiol, eugenol, vinyl acetic acid and N,N-dimethylformamide is (5-12):(8.2-16.4):(4.3-8.6):(100-120); The intermediate product is added to ethanol, and then N'N-dicyclohexyl diimide and N-hydroxysuccinimide are added, and stirred for 1-2 hours, and then the aminated polyacrylonitrile / aerogel composite fiber is added under stirring conditions, and the reaction is stirred for 22-26 hours in a nitrogen atmosphere. During the reaction, the pH of the reaction system is adjusted to 5.4-5.6 by using a 1 mol / L hydrochloric acid aqueous solution. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a low thermal conductivity UV-resistant fiber; wherein the mass ratio of the intermediate product, ethanol, N'N-dicyclohexyl diimide, N-hydroxysuccinimide, and aminated polyacrylonitrile / aerogel composite fiber is (3-6):(80-120):(3.7-7.4):(2.1-4.2):(3-4); In the above process, the two ends of 1,2-ethanedithiol react with the carbon-carbon double bonds of eugenol and vinyl acetic acid respectively to obtain an intermediate product; the carboxyl group in the intermediate product undergoes an amidation reaction with the amino group of the aminated polyacrylonitrile / aerogel composite fiber to obtain a low thermal conductivity UV-resistant fiber.
[0014] The low thermal conductivity anti-ultraviolet fiber is prepared by the method for preparing the low thermal conductivity anti-ultraviolet fiber.
[0015] Application of the low thermal conductivity anti-ultraviolet fiber to light-shielding and heat-shielding fabrics.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses modified cellulose-based aerogel as the core layer and polyacrylonitrile as the skin layer to prepare polyacrylonitrile / aerogel composite fibers by spinning. The rich pore structure and developed three-dimensional network structure inside the composite fibers can trap a large amount of static air, reduce the heat transfer inside the composite fibers, and thus improve the thermal conductivity of the polyacrylonitrile / aerogel composite fibers; The modified cellulose-based aerogel of the present invention is added with NH 2- MIL-125(Ti), and poly(ethylene glycol) chloride as a crosslinker, NH 2- MIL-125(Ti) nanoparticles fill the network structure of aerogels, making the structure more compact, thereby improving the mechanical strength of aerogels. 2-MIL-125(Ti) gives aerogel good UV resistance due to its own UV blocking properties, and NH 2- The porous structure of MIL-125(Ti) enriches the pore structure of the aerogel and reduces the thermal conductivity of the aerogel. The chlorinated polyethylene glycol obtained by the modification of polyethylene glycol with a molecular weight of 600 has a longer chain structure and cross-links with cellulose nanofibers to improve the strength and toughness of the aerogel. Secondary pores are formed during the cross-linking process, which increases the porosity of the aerogel and further reduces the thermal conductivity of the aerogel. In addition, the chlorinated polyethylene glycol cross-linking agent and NH 2- MIL-125(Ti) and modified cellulose nanofibers are combined in the form of chemical bonds, which improves the connection strength between the three and gives the aerogel better performance; The present invention adds a composite nano material to the polyacrylonitrile skin layer. The composite nano material uses a porous zinc oxide nano sheet as a matrix. The porous zinc oxide nano sheet not only has good anti-ultraviolet performance, but also has a high porosity, which can improve the heat insulation effect of the polyacrylonitrile / aerogel composite fiber and reduce the thermal conductivity. Polydopamine doped with thiol heterocycles is formed on the surface of the porous zinc oxide nano sheet to obtain a surface-modified porous zinc oxide nano sheet. The polydopamine itself has a good ultraviolet absorption and shielding effect. After the thiol heterocycle is doped, the formation of a conjugated structure in the polydopamine is effectively hindered and destroyed, and a donor-donor intermediate with a large band gap is formed, thereby enhancing the ultraviolet absorption effect of the polydopamine. The surface-modified porous zinc oxide nano sheet is treated with citric acid. The zinc oxide nanosheets are treated and multiple carboxyl groups are introduced into the surface modified porous zinc oxide nanosheets. The introduction of carboxyl groups increases the anchoring binding sites for the subsequent growth of cobalt borate nanosheets. The Lewis groups on the cobalt borate nanosheets combine with the strongly electronegative nitrile groups in polyacrylonitrile, so that the composite nanomaterials can form a strong interaction with polyacrylonitrile, improve the dispersibility of the composite nanomaterials in the polyacrylonitrile cortex, and make the cortex have good thermal insulation, UV resistance and mechanical properties. In addition, the cobalt borate nanosheets can release water molecules and generate metal oxides or borides during the combustion process, which dilutes the combustible gas while converting the carbon monoxide in the toxic smoke into carbon dioxide, reducing the toxicity of the smoke and achieving a certain flame retardant effect.
[0017] Therefore, the polyacrylonitrile / aerogel composite fiber of the present invention has the advantages of low thermal conductivity, good anti-ultraviolet flame retardant effect and excellent mechanical properties.
[0018] 2. The present invention obtains low thermal conductivity anti-ultraviolet fiber by aminating polyacrylonitrile / aerogel composite fiber and then combining it with an intermediate product; the active group amino group is introduced into the surface of the polyacrylonitrile / aerogel composite fiber by aminating the polyacrylonitrile / aerogel composite fiber, but the mechanical properties of the composite fiber are slightly decreased. However, after reacting with the intermediate product, the intermolecular force is enhanced, so that the mechanical properties of the composite fiber are improved; more importantly, flame-retardant nitrogen and sulfur elements and eugenol structure with ultraviolet absorption effect are introduced into the surface of the composite fiber through amination and grafting of the intermediate product, which cooperates with the composite nanomaterial to further improve the flame retardant and ultraviolet resistance of the low thermal conductivity anti-ultraviolet fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a process flow chart of a method for preparing low thermal conductivity UV-resistant fiber of the present invention; Figure 2 It is a comparison chart of tensile strength test of low thermal conductivity anti-ultraviolet fiber prepared by Examples 2-4 of the present invention and Comparative Examples 3-8; Figure 3 It is a comparison chart of thermal conductivity test of low thermal conductivity anti-ultraviolet fibers prepared in Examples 2-4 of the present invention and Comparative Examples 3-8; Figure 4 It is a UPF test comparison chart of low thermal conductivity anti-ultraviolet fibers prepared in Examples 2-4 of the present invention and Comparative Examples 3-8; Figure 5 It is a comparison chart of LOI tests of low thermal conductivity UV-resistant fibers prepared in Examples 2-4 of the present invention and Comparative Examples 3-8. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example
[0021] This embodiment discloses a method for preparing a modified cellulose-based aerogel powder, comprising the following steps: Step S1, taking 125 g of 1 wt% cellulose nanofiber aqueous dispersion, adding 2 g of sodium periodate thereto, stirring for 48 h at room temperature in the dark, filtering, washing, and drying to obtain pretreated cellulose nanofibers; 1.1 g of hexamethylenediamine was added to 225 mL of a 0.5 wt % aqueous dispersion of pretreated cellulose nanofibers, and the mixture was stirred at 30° C. for 6 h, filtered, washed, and dried to obtain modified cellulose nanofibers. Step S2, adding 4.5 g of polyethylene glycol to 110 g of dichloromethane, and then adding 5.5 g of maleic anhydride and 0.08 g of 4-dimethylaminopyridine, stirring and reacting at room temperature for 75 h, after the reaction is completed, precipitating the product with ether, washing, and drying to obtain dicarboxylated polyethylene glycol; 5 g of dicarboxylated polyethylene glycol, 2.3 g of 3-hydroxyglutaric acid, 0.07 g of p-toluenesulfonic acid, and 90 g of N,N-dimethylformamide were mixed, heated to 125° C. in a nitrogen atmosphere, and stirred for reaction for 4 h. After the reaction was completed, the solvent was removed by rotary evaporation at 85° C. to obtain polycarboxylated polyethylene glycol; Mix 5g of polycarboxylated polyethylene glycol, 6.5g of thionyl chloride, and 110g of N,N-dimethylformamide, heat to 60°C and maintain for 24h, and after the reaction is completed, perform rotary evaporation at 85°C to obtain chlorinated polyethylene glycol; Take 4.2g of 2-aminoterephthalic acid and dissolve it in a mixed solution of 56.7g of N,N-dimethylformamide and 12g of methanol, stir for 30min, then add 4.5g of titanium isopropoxide, continue stirring for 30min, heat to 110℃ in a sealed environment for hydrothermal reaction for 75h, cool naturally to room temperature after the reaction, filter, wash the filter cake with N,N-dimethylformamide and methanol respectively by centrifugation for 3 times, dry at 55℃ for 11h, grind, and obtain NH 2- MIL-125(Ti); NH 2- MIL-125(Ti) was added to a suspension of modified cellulose nanofibers with a mass fraction of 2.3 wt%, stirred for 12 h, and freeze-dried at -45 °C for 48 h to obtain a cellulose-based aerogel, in which NH 2- The mass ratio of MIL-125(Ti) and modified cellulose nanofibers was 0.8:1; Polyethylene glycol chloride is added to acetone and then added to cellulose-based aerogel, and a cross-linking reaction is carried out at 90°C for 24 hours. Then, the aerogel is washed with acetone, vacuum dried at 55°C, and ground to obtain modified cellulose-based aerogel powder; wherein the mass ratio of polyethylene glycol chloride, acetone, and cellulose-based aerogel is 1:50:4. Example 2
[0022] This embodiment discloses a method for preparing a low thermal conductivity UV-resistant fiber, comprising the following steps: Step (1), dispersing zinc nitrate and hexamethylenetetramine in deionized water, stirring to obtain a mixed solution, wherein the concentration of zinc ions in the mixed solution is 0.1 mol / L, and the molar ratio of zinc ions to hexamethylenetetramine is 1:1; storing the mixed solution in an oven at 85° C. for 6 days, collecting the precipitate, washing, air-drying at room temperature, and heating to 240° C. at a heating rate of 8° C. / min in an air atmosphere and maintaining for 70 minutes to obtain a porous zinc oxide nanosheet; 32 g of ethanol, 45 g of deionized water, 0.4 mL of 28 wt% ammonia solution, and 3 g of porous zinc oxide nanosheets were mixed, stirred at room temperature for 20 min, and then 3 g of 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and 15 mL of 0.05 g / mL dopamine hydrochloride aqueous solution were added, and the reaction was continued with stirring for 22 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain surface-modified porous zinc oxide nanosheets; 4 g of surface-modified porous zinc oxide nanosheets, 3.5 g of citric acid, 0.09 g of p-toluenesulfonic acid, and 150 g of N,N-dimethylformamide were mixed, heated to 120°C in a nitrogen atmosphere, and stirred for reaction for 5 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain functionalized zinc oxide nanosheets; Step (2), adding 1.5 g of cobalt nitrate hexahydrate to 500 g of deionized water at a stirring speed of 600 r / min, then adding 100 mL of a 3 mg / mL aqueous dispersion of functionalized zinc oxide nanosheets, continuing stirring for 20 min, then adding 30 mL of a 0.5 mol / L aqueous sodium borohydride solution, stirring for 30 min, centrifuging, collecting and washing the precipitate, and then vacuum drying at 60° C. for 15 h to obtain a composite nanomaterial; At 70°C, polyacrylonitrile was added to N,N-dimethylformamide, and stirred until all the solids were dissolved, and then the composite nanomaterial was added, and the stirring was continued for 50 minutes to obtain a cortex spinning solution; wherein the mass ratio of polyacrylonitrile, N,N-dimethylformamide, and the composite nanomaterial was 1:9:0.1; Step (3), adding the modified cellulose-based aerogel powder into N,N-dimethylformamide, and ultrasonically treating for 1 hour to obtain a core layer spinning solution with a concentration of 2 mg / mL; The cortex spinning solution and the core spinning solution were used as raw materials for spinning to obtain polyacrylonitrile / aerogel composite fibers; wherein the feeding rate of the cortex spinning solution was 12 mL / h, the feeding rate of the core spinning solution was 2 mL / h, the spinning high-speed airflow drafting pressure was 0.2 MPa, the receiving distance was 60 cm, and the spinning time was 8 h; The polyacrylonitrile / aerogel composite fiber was immersed in a 35wt% diethylenetriamine aqueous solution with a bath ratio of 1:25, heated to 100°C, stirred for reaction for 3h, filtered, washed, and dried to obtain an aminated polyacrylonitrile / aerogel composite fiber; Step (4), 5 g of 1,2-ethanedithiol, 8.2 g of eugenol, 4.3 g of vinyl acetic acid, and 100 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 4 h. After the reaction was completed, the mixture was rotary evaporated at 80° C. to obtain an intermediate product; 3 g of the intermediate product was added to 80 g of ethanol, and then 3.7 g of N'N-dicyclohexyl diimide and 2.1 g of N-hydroxysuccinimide were added, stirred for 1 hour, and then 3 g of aminated polyacrylonitrile / aerogel composite fiber was added under stirring conditions. The reaction was stirred for 22 hours in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.4 with a 1 mol / L hydrochloric acid aqueous solution. After the reaction, centrifuged, washed, and dried to obtain a low thermal conductivity UV-resistant fiber. Example 3
[0023] This embodiment discloses a method for preparing a low thermal conductivity UV-resistant fiber, comprising the following steps: Step (1), dispersing zinc nitrate and hexamethylenetetramine in deionized water, stirring to obtain a mixed solution, wherein the concentration of zinc ions in the mixed solution is 0.3 mol / L, and the molar ratio of zinc ions to hexamethylenetetramine is 1:1; storing the mixed solution in an oven at 95° C. for 6 days, collecting the precipitate, washing, air-drying at room temperature, and heating to 260° C. in an air atmosphere at a heating rate of 10° C. / min and maintaining for 50 minutes to obtain a porous zinc oxide nanosheet; 64 g of ethanol, 90 g of deionized water, 0.8 mL of 28 wt% ammonia solution, and 8 g of porous zinc oxide nanosheets were mixed, stirred at room temperature for 40 min, and then 5 g of 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and 25 mL of 0.05 g / mL dopamine hydrochloride aqueous solution were added, and the reaction was continued with stirring for 22 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain surface-modified porous zinc oxide nanosheets; 6 g of surface-modified porous zinc oxide nanosheets, 5.5 g of citric acid, 0.12 g of p-toluenesulfonic acid, and 200 g of N,N-dimethylformamide were mixed, heated to 140°C in a nitrogen atmosphere, and stirred for reaction for 3 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain functionalized zinc oxide nanosheets; Step (2), adding 3 g of cobalt nitrate hexahydrate to 800 g of deionized water at a stirring speed of 700 r / min, then adding 200 mL of a 3 mg / mL aqueous dispersion of functionalized zinc oxide nanosheets, continuing stirring for 40 min, then adding 60 mL of a 0.5 mol / L sodium borohydride aqueous solution, stirring for 50 min, centrifuging, collecting and washing the precipitate, and then vacuum drying at 80° C. for 10 h to obtain a composite nanomaterial; At 80°C, polyacrylonitrile was added to N,N-dimethylformamide, and stirred until all the solids were dissolved, and then the composite nanomaterial was added, and the stirring was continued for 70 minutes to obtain a cortex spinning solution; wherein the mass ratio of polyacrylonitrile, N,N-dimethylformamide, and the composite nanomaterial was 1:9:0.3; Step (3), adding the modified cellulose-based aerogel powder into N,N-dimethylformamide, and ultrasonically treating for 1.5 h to obtain a core layer spinning solution with a concentration of 6 mg / mL; The cortex spinning solution and the core spinning solution were used as raw materials for spinning to obtain polyacrylonitrile / aerogel composite fibers; wherein the feeding rate of the cortex spinning solution was 12 mL / h, the feeding rate of the core spinning solution was 2 mL / h, the spinning high-speed airflow drafting pressure was 0.2 MPa, the receiving distance was 60 cm, and the spinning time was 8 h; The polyacrylonitrile / aerogel composite fiber was immersed in a 35wt% diethylenetriamine aqueous solution with a bath ratio of 1:35, heated to 120°C, stirred for reaction for 2h, filtered, washed, and dried to obtain an aminated polyacrylonitrile / aerogel composite fiber; Step (4), 12 g of 1,2-ethanedithiol, 16.4 g of eugenol, 8.6 g of vinyl acetic acid, and 120 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 5 h. After the reaction was completed, the mixture was rotary evaporated at 90° C. to obtain an intermediate product; 6 g of the intermediate product was added to 120 g of ethanol, and then 7.4 g of N'N-dicyclohexyl diimide and 4.2 g of N-hydroxysuccinimide were added, and stirred for 2 h. Then, 4 g of aminated polyacrylonitrile / aerogel composite fiber was added under stirring conditions. The reaction was stirred for 26 h in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.6 with a 1 mol / L hydrochloric acid aqueous solution. After the reaction, the reaction was centrifuged, washed, and dried to obtain a low thermal conductivity UV-resistant fiber. Example 4
[0024] This embodiment discloses a method for preparing a low thermal conductivity UV-resistant fiber, comprising the following steps: Step (1), dispersing zinc nitrate and hexamethylenetetramine in deionized water, stirring to obtain a mixed solution, wherein the concentration of zinc ions in the mixed solution is 0.2 mol / L, and the molar ratio of zinc ions to hexamethylenetetramine is 1:1; storing the mixed solution in an oven at 90° C. for 6 days, collecting the precipitate, washing, air-drying at room temperature, and heating to 250° C. in an air atmosphere at a heating rate of 9° C. / min and maintaining for 60 minutes to obtain porous zinc oxide nanosheets; 48 g of ethanol, 67.5 g of deionized water, 0.6 mL of 28 wt% ammonia solution, and 5.5 g of porous zinc oxide nanosheets were mixed, stirred at room temperature for 30 min, and then 4 g of 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and 20 mL of 0.05 g / mL dopamine hydrochloride aqueous solution were added, and the reaction was continued with stirring for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain surface-modified porous zinc oxide nanosheets; 5 g of surface-modified porous zinc oxide nanosheets, 4.5 g of citric acid, 0.1 g of p-toluenesulfonic acid, and 175 g of N,N-dimethylformamide were mixed, heated to 130°C in a nitrogen atmosphere, and stirred for reaction for 4 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain functionalized zinc oxide nanosheets; Step (2), adding 2.3 g of cobalt nitrate hexahydrate to 650 g of deionized water at a stirring speed of 650 r / min, then adding 150 mL of a 3 mg / mL aqueous dispersion of functionalized zinc oxide nanosheets, continuing stirring for 30 min, then adding 45 mL of a 0.5 mol / L aqueous sodium borohydride solution, stirring for 40 min, centrifuging, collecting and washing the precipitate, and then vacuum drying at 70° C. for 12 h to obtain a composite nanomaterial; At 75°C, polyacrylonitrile was added to N,N-dimethylformamide, and stirred until all the solids were dissolved, and then the composite nanomaterial was added, and the stirring was continued for 60 minutes to obtain a cortex spinning solution; wherein the mass ratio of polyacrylonitrile, N,N-dimethylformamide, and the composite nanomaterial was 1:9:0.2; Step (3), adding the modified cellulose-based aerogel powder into N,N-dimethylformamide, and ultrasonically treating for 1.2 h to obtain a core layer spinning solution with a concentration of 4 mg / mL; The cortex spinning solution and the core spinning solution were used as raw materials for spinning to obtain polyacrylonitrile / aerogel composite fibers; wherein the feeding rate of the cortex spinning solution was 12 mL / h, the feeding rate of the core spinning solution was 2 mL / h, the spinning high-speed airflow drafting pressure was 0.2 MPa, the receiving distance was 60 cm, and the spinning time was 8 h; The polyacrylonitrile / aerogel composite fiber was immersed in a 35wt% diethylenetriamine aqueous solution with a bath ratio of 1:30, heated to 110°C, stirred for reaction for 2.5h, filtered, washed, and dried to obtain an aminated polyacrylonitrile / aerogel composite fiber; Step (4), 8.5 g of 1,2-ethanedithiol, 12.3 g of eugenol, 6.5 g of vinyl acetic acid, and 110 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 4.5 h. After the reaction was completed, the mixture was rotary evaporated at 85° C. to obtain an intermediate product; 4.5 g of the intermediate product was added to 100 g of ethanol, and then 5.6 g of N'N-dicyclohexyl diimide and 3.2 g of N-hydroxysuccinimide were added, and stirred for 1.5 h. Then, 3.5 g of aminated polyacrylonitrile / aerogel composite fiber was added under stirring. The reaction was stirred for 24 h in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.5 with a 1 mol / L aqueous hydrochloric acid solution. After the reaction, the reaction was centrifuged, washed, and dried to obtain a low thermal conductivity UV-resistant fiber.
[0025] The modified cellulose-based aerogel powder used in the above Examples 2-4 is the modified cellulose-based aerogel powder prepared in Example 1.
[0026] Comparative Example 1 Compared with Example 1, in the process of preparing cellulose-based aerogel in Comparative Example 1, NH 2- MIL-125(Ti), other conditions remain unchanged.
[0027] Comparative Example 2 Compared with Example 1, in the process of preparing the modified cellulose-based aerogel powder in Comparative Example 2, polyethylene glycol was used instead of chlorinated polyethylene glycol, and other conditions remained unchanged.
[0028] Comparative Example 3 Compared with Example 4, in the process of preparing the core layer spinning solution in Comparative Example 3, the modified cellulose-based aerogel powder prepared in Comparative Example 1 was used, and other conditions remained unchanged.
[0029] Comparative Example 4 Compared with Example 4, in the process of preparing the core layer spinning solution in Comparative Example 4, the modified cellulose-based aerogel powder prepared in Comparative Example 2 was used, and other conditions remained unchanged.
[0030] Comparative Example 5 Compared with Example 4, in Comparative Example 5, during the preparation of the core layer spinning solution, cellulose-based aerogel powder was used instead of modified cellulose-based aerogel powder, and other conditions remained unchanged.
[0031] Comparative Example 6 Compared with Example 4, in the process of preparing the surface-modified porous zinc oxide nanosheets in Comparative Example 6, 2-mercapto-5-methoxyimidazo[4.5-b]pyridine was not added, and other conditions remained unchanged.
[0032] Comparative Example 7 Compared with Example 4, in Comparative Example 7, in the process of preparing the cortical spinning solution, functionalized zinc oxide nanosheets were used instead of the composite nanomaterial, and other conditions remained unchanged.
[0033] Comparative Example 8 Compared with Example 4, the polyacrylonitrile / aerogel composite fiber of Comparative Example 8 is not subjected to amination treatment and intermediate product grafting, that is, the polyacrylonitrile / aerogel composite fiber in this comparative example is the final product, low thermal conductivity, UV-resistant fiber, and other conditions remain unchanged.
[0034] In the above embodiments and comparative examples, polyacrylonitrile, with a molecular weight of 150,000 and a viscosity of 500 mPas, comes from Dongguan Haosheng Plastic Raw Materials Co., Ltd.; polyethylene glycol, with an average molecular weight of 600, comes from Guangzhou Taili Chemical Co., Ltd.; and cellulose nanofibers, with a diameter of 10-80 nm and a length of 800-3000 nm, come from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.
[0035] Experimental example The performance of the low thermal conductivity UV-resistant fibers prepared in Examples 2-4 and Comparative Examples 3-8 was tested.
[0036] 1. Mechanical properties test: According to the standard GB 13022-1991, a universal testing machine is used to test the mechanical properties of each group of samples. The instrument is an electronic universal testing machine (non-metallic direction), model CMT4202 / ZWICK / Z020.
[0037] 2. Thermal conductivity test: According to the standard ISO 22007-2 / ASTME 1530 "Introduction to thermal conductivity test method", the thermal conductivity of each group of samples at 80°C was determined using the TPS2500S thermal constant analyzer and the double helix probe planar heat source method.
[0038] 3. Anti-ultraviolet performance test: Weave each group of samples to obtain a weight of 115g / m 2 For light-shielding and heat-shielding fabrics, the ultraviolet protection factor (UPF) of each group of fabric samples was tested with reference to AATCC 183-2010.
[0039] 4. Flame retardant performance test: According to ASTM D2863-2017, the limiting oxygen index (LOI) was measured on a LOI analyzer (model JF-3).
[0040] The test results are shown in Table 1: Table 1 Tensile strength (MPa) Thermal conductivity W / (mK) UPF LOI% Example 2 4.6 0.0273 70.93 37.6 Example 3 5.2 0.0184 72.04 38.9 Example 4 4.8 0.0236 71.22 38.2 Comparative Example 3 3.3 0.0327 66.89 38.2 Comparative Example 4 4.4 0.0303 71.22 38.1 Comparative Example 5 3.8 0.0331 71.21 38.2 Comparative Example 6 4.8 0.0235 68.46 38.2 Comparative Example 7 3.4 0.0281 70.85 37.1 Comparative Example 8 4.1 0.0236 66.91 36.3 From the test results in Table 1, it can be seen that the low thermal conductivity anti-ultraviolet fibers prepared in Examples 2-4 of the present invention have the advantages of low thermal conductivity, good anti-ultraviolet flame retardant effect, and good mechanical properties. 2- MIL-125(Ti) nanoparticles fill the network structure of aerogels, making the structure more compact, thereby improving the mechanical strength of aerogels. 2- MIL-125 (Ti) has good UV resistance and low thermal conductivity due to its own UV blocking performance and porous structure. Comparison between Comparative Examples 4-5 and Example 4 shows that the chlorinated polyethylene glycol obtained by modification with a molecular weight of 600 has a longer chain structure, which can improve the strength and toughness of the aerogel and form secondary pores during the crosslinking process, thereby improving the porosity of the aerogel and further reducing the thermal conductivity of the aerogel. The polyethylene glycol is chlorinated to make it react with NH 2- MIL-125 (Ti) and modified cellulose nanofibers are combined in the form of chemical bonds to improve the cross-linking modification effect; from the comparison of comparative example 6 and embodiment 4, it can be seen that thiol heterocycle-doped polydopamine is formed on the surface of the porous zinc oxide nanosheet to form a surface-modified porous zinc oxide nanosheet, and thiol heterocycle doping can enhance the ultraviolet absorption effect of polydopamine, thereby improving the anti-ultraviolet performance of the fiber; from the comparison of comparative example 7 and embodiment 4, it can be seen that multiple carboxyl groups are introduced on the surface-modified porous zinc oxide nanosheet, and then cobalt borate nanosheets are grown in situ, and the cobalt borate nanosheets can form a strong interaction between the composite nanomaterials and polyacrylonitrile. , improving the dispersibility of the composite nanomaterial in the polyacrylonitrile cortex, so that the cortex has good thermal insulation, UV resistance and mechanical properties; in addition, the cobalt borate nanosheets can release water molecules and generate metal oxides or borides during the combustion process, dilute the combustible gas, and improve the flame retardant effect; from the comparison between comparative example 8 and embodiment 4, it can be seen that after the polyacrylonitrile / aerogel composite fiber is aminized and the intermediate product is grafted, the intermolecular force is enhanced, the mechanical properties are improved, and the introduction of flame retardant nitrogen and sulfur elements and a eugenol structure with UV absorption effect further improves the flame retardant and UV resistance of the low thermal conductivity UV-resistant fiber.
[0041] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low thermal conductivity UV-resistant fiber, characterized in that: The following steps are involved: Step (1), using zinc nitrate and hexamethylenetetramine as raw materials to prepare porous zinc oxide nanosheets; the porous zinc oxide nanosheets are subjected to surface modification and functionalization treatment to obtain functionalized zinc oxide nanosheets; Step (2), in situ growing cobalt borate on the surface of the functionalized zinc oxide nanosheet to obtain a composite nanomaterial; mixing polyacrylonitrile, N,N-dimethylformamide and the composite nanomaterial to obtain a cortical spinning solution; Step (3), mixing modified cellulose-based aerogel powder and N,N-dimethylformamide to obtain a core layer spinning solution; spinning the skin layer spinning solution and the core layer spinning solution as raw materials to obtain polyacrylonitrile / aerogel composite fibers; modifying the polyacrylonitrile / aerogel composite fibers with diethylenetriamine to obtain aminated polyacrylonitrile / aerogel composite fibers; The method for preparing the modified cellulose-based aerogel powder comprises the following steps: Step S1, the cellulose nanofibers are pretreated and then reacted with hexamethylenediamine to obtain modified cellulose nanofibers; Step S2, treating polyethylene glycol to obtain chlorinated polyethylene glycol; Preparation of NH by hydrothermal method 2- MIL-125(Ti); modified cellulose nanofibers, NH 2- MIL-125(Ti) was used to prepare cellulose-based aerogel, and the cellulose-based aerogel was cross-linked and modified by poly(ethylene glycol) chloride to obtain modified cellulose-based aerogel powder; Step (4), 1,2-ethanedithiol, eugenol, and vinyl acetic acid react to obtain an intermediate product, and the intermediate product is used to modify the aminated polyacrylonitrile / aerogel composite fiber to obtain a low thermal conductivity UV-resistant fiber.
2. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (1), the preparation method of the functionalized zinc oxide nanosheets comprises: dispersing zinc nitrate and hexamethylenetetramine in deionized water, stirring to obtain a mixed solution, wherein the concentration of zinc ions in the mixed solution is 0.1-0.3 mol / L, and the molar ratio of zinc ions to hexamethylenetetramine is 1:1; storing the mixed solution in an oven at 85-95°C for 6 days, collecting the precipitate, washing, air-drying at room temperature, and heating to 240-260°C in an air atmosphere at a heating rate of 8-10°C / min and maintaining for 50-70 minutes to obtain porous zinc oxide nanosheets; Ethanol, deionized water, 28 wt% ammonia solution, and porous zinc oxide nanosheets are mixed, stirred at room temperature for 20-40 min, and then 2-mercapto-5-methoxyimidazo[4.5-b]pyridine and 0.05 g / mL dopamine hydrochloride aqueous solution are added, and the reaction is continued with stirring for 22-26 h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain surface-modified porous zinc oxide nanosheets; wherein the amount ratio of ethanol, deionized water, ammonia solution, porous zinc oxide nanosheets, 2-mercapto-5-methoxyimidazo[4.5-b]pyridine, and dopamine hydrochloride aqueous solution is (32-64) g: (45-90) g: (0.4-0.8) mL: (3-8) g: (3-5) g: (15-25) mL; Surface modified porous zinc oxide nanosheets, citric acid, p-toluenesulfonic acid, and N,N-dimethylformamide are mixed, heated to 120-140°C in a nitrogen atmosphere, and stirred for reaction for 3-5 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain functionalized zinc oxide nanosheets; wherein the mass ratio of surface modified porous zinc oxide nanosheets, citric acid, p-toluenesulfonic acid, and N,N-dimethylformamide is (4-6):(3.5-5.5):(0.09-0.12):(150-200).
3. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (2), the preparation method of the composite nanomaterial is as follows: at a stirring speed of 600-700 r / min, cobalt nitrate hexahydrate is added to deionized water, and then a functionalized zinc oxide nanosheet aqueous dispersion with a concentration of 3 mg / mL is added, stirring is continued for 20-40 minutes, and then a sodium borohydride aqueous solution with a concentration of 0.5 mol / L is added, stirring and reacting for 30-50 minutes, centrifuging, collecting and washing the precipitate, and drying to obtain the composite nanomaterial; wherein the amount ratio of cobalt nitrate hexahydrate, deionized water, functionalized zinc oxide nanosheet aqueous dispersion, and sodium borohydride aqueous solution is (1.5-3) g: (500-800) g: (100-200) mL: (30-60) mL.
4. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (2), in the skin spinning solution, the mass ratio of polyacrylonitrile, N,N-dimethylformamide and composite nanomaterial is 1:9:(0.1-0.3).
5. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (3), the concentration of the core layer spinning solution is 2-6 mg / mL; the spinning conditions are: the feed rate of the skin layer spinning solution is 12 mL / h, the feed rate of the core layer spinning solution is 2 mL / h, the spinning high-speed airflow drawing pressure is 0.2 MPa, the receiving distance is 60 cm, and the spinning time is 8 h.
6. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (3), the preparation method of the aminated polyacrylonitrile / aerogel composite fiber is as follows: the polyacrylonitrile / aerogel composite fiber is immersed in a 35wt% diethylenetriamine aqueous solution with a bath ratio of 1:(25-35), heated to 100-120°C, stirred for reaction for 2-3h, filtered, washed, and dried to obtain the aminated polyacrylonitrile / aerogel composite fiber.
7. The method for preparing the low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In step (3), the method for preparing the modified cellulose-based aerogel powder comprises the following steps: Step S1, taking a 1wt% cellulose nanofiber aqueous dispersion, adding sodium periodate thereto, stirring in the dark at room temperature for 45-50h, filtering, washing, and drying to obtain pretreated cellulose nanofibers; wherein the mass ratio of the cellulose nanofiber aqueous dispersion to the sodium periodate is (100-150):(1.6-2.4); Add hexamethylenediamine to a 0.5 wt% aqueous dispersion of pretreated cellulose nanofibers, stir and react at 28-32° C. for 5.5-6.5 h, filter, wash, and dry to obtain modified cellulose nanofibers; wherein the amount ratio of the aqueous dispersion of the pretreated cellulose nanofibers to hexamethylenediamine is (200-250) mL: (0.9-1.2) g; Step S2, adding polyethylene glycol to dichloromethane, and then adding maleic anhydride and 4-dimethylaminopyridine, stirring and reacting at room temperature for 70-80 hours, and after the reaction is completed, precipitating the product with ether, washing, and drying to obtain dicarboxylated polyethylene glycol; wherein the mass ratio of polyethylene glycol, dichloromethane, maleic anhydride, and 4-dimethylaminopyridine is (3-6):(100-120):(4-7):(0.05-0.1); Dicarboxylated polyethylene glycol, 3-hydroxyglutaric acid, p-toluenesulfonic acid and N,N-dimethylformamide are mixed, heated to 120-130° C. in a nitrogen atmosphere, stirred for reaction for 3-5 hours, and after the reaction is completed, rotary evaporation is performed to obtain polycarboxylated polyethylene glycol; wherein the mass ratio of dicarboxylated polyethylene glycol, 3-hydroxyglutaric acid, p-toluenesulfonic acid and N,N-dimethylformamide is (3.3-6.6):(1.5-3):(0.05-0.08):(80-100); Mix polycarboxylated polyethylene glycol, thionyl chloride and N,N-dimethylformamide, heat to 55-65°C and maintain for 20-28 hours, and after the reaction is completed, rotary evaporate to obtain chlorinated polyethylene glycol; wherein the mass ratio of polycarboxylated polyethylene glycol, thionyl chloride and N,N-dimethylformamide is (4-6):(5-8):(100-120); Dissolve 2-aminoterephthalic acid in a mixed solution of N,N-dimethylformamide and methanol, stir for 20-40 minutes, then add titanium isopropoxide, continue stirring for 20-40 minutes, heat to 100-120°C in a sealed environment, perform hydrothermal reaction for 70-80 hours, cool naturally to room temperature after the reaction, filter, wash, dry, grind, and obtain NH 2- MIL-125(Ti); wherein the mass ratio of 2-aminoterephthalic acid, N,N-dimethylformamide, methanol, and titanium isopropoxide is (2.8-5.6):(37.8-75.6):(8-16):(3-6); NH 2- MIL-125(Ti) was added to a suspension of modified cellulose nanofibers with a mass fraction of 1-1.5wt%, stirred for 10-15h, and freeze-dried at (-48)-(-42)℃ for 45-50h to obtain a cellulose-based aerogel, wherein NH 2- The mass ratio of MIL-125(Ti) and modified cellulose nanofibers is (0.5-0.1):1; The chlorinated polyethylene glycol is added to acetone and then added to the cellulose-based aerogel, and a cross-linking reaction is carried out at 85-95°C for 20-28h. Then, the aerogel is washed with acetone, vacuum dried at 50-60°C, and ground to obtain a modified cellulose-based aerogel powder; wherein the mass ratio of the chlorinated polyethylene glycol, acetone, and cellulose-based aerogel is (0.8-1.2):50:
4.
8. The method for preparing low thermal conductivity UV-resistant fiber according to claim 1, characterized in that: In the step (4), the method for preparing the low thermal conductivity UV-resistant fiber is as follows: 1,2-ethanedithiol, eugenol, vinyl acetic acid, and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 4-5 hours, and after the reaction is completed, rotary evaporation is performed to obtain an intermediate product; wherein the mass ratio of 1,2-ethanedithiol, eugenol, vinyl acetic acid, and N,N-dimethylformamide is (5-12):(8.2-16.4):(4.3-8.6):(100-120); The intermediate product is added to ethanol, and then N'N-dicyclohexyl diimide and N-hydroxysuccinimide are added, stirred for 1-2 hours, and then the aminated polyacrylonitrile / aerogel composite fiber is added under stirring conditions, and the reaction is stirred for 22-26 hours in a nitrogen atmosphere. During the reaction, the pH of the reaction system is adjusted to 5.4-5.6 by using a 1 mol / L hydrochloric acid aqueous solution. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a low thermal conductivity UV-resistant fiber; wherein the mass ratio of the intermediate product, ethanol, N'N-dicyclohexyl diimide, N-hydroxysuccinimide, and aminated polyacrylonitrile / aerogel composite fiber is (3-6):(80-120):(3.7-7.4):(2.1-4.2):(3-4).
9. A low thermal conductivity anti-ultraviolet fiber prepared by the method for preparing a low thermal conductivity anti-ultraviolet fiber according to any one of claims 1 to 8.
10. Use of the low thermal conductivity anti-ultraviolet fiber according to claim 9 in light-shielding and heat-shielding fabrics.
Citation Information
Patent Citations
Anti-ultraviolet ray fibers
CN106637491A
Cellulose / SiO2 hybrid aerogel fiber and preparation method thereof
CN114855291A
Anti-ultraviolet moisture absorption fiber and preparation method thereof
CN118979315A
Cited By
Light-color warm-keeping fiber, preparation method and application of light-color warm-keeping fiber to fabric
CN121538751A
A light colour thermal fibre, a method of manufacture and use on a fabric
CN121538751B